Bottoms [videorecording (Blu-Ray)] - Seligman, Emma (Film director); Sennott, Rachel, 1995-; Sennott, Rachel, 1995-; Edebiri, Ayo, 1995-; Cruz, Ruby; Liu, Havana Rose, 1997-; Gerber, Kaia, 2001-; Lynch, Marshawn, 1986-; Galitzine, Nicholas; Fowler, Miles; Dominczyk, Dagmara, 1976- (Kino Lorber, 2025)
In this refreshingly unique comedy directed by Emma Seligman, two girls, PJ and Josie, start a fight club as a way to lose their virginity to cheerleaders. And their bizarre plan works! The fight club gains traction, and soon the most popular girls in school are beating each other up in the name of self-defense. But PJ and Josie find themselves in over their heads and in need of a way out before their plan is exposed.